2014
DOI: 10.1177/2158244014537085
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Effect of Communication Skills Training for Married Women on Couples’ Intimacy and Quality of Life

Abstract: The aim of this study was to investigate the effect of communication skills education for married women on couples’ intimacy and quality of life. The subjects of this study were married female students enrolled in the spring semester of 2011 at the Applied Sciences and Technology University (Tourism Unit) of Kerman in Iran, along with their husbands. Of the students who expressed interest in taking part in this study, 30 subjects were selected and randomly assigned to either an experimental or a control group.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 19 publications
(31 reference statements)
1
8
0
1
Order By: Relevance
“…The results of this study are consistent with the findings of other studies (18,19,44). Given the importance of communication and the method for the transfer of a message, communication skill enables couples to convey their messages more clearly and evade behaviors that may lead to the reduction of marital intimacy and satisfaction such as contempt, criticism, blame, and sarcasm (8).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of this study are consistent with the findings of other studies (18,19,44). Given the importance of communication and the method for the transfer of a message, communication skill enables couples to convey their messages more clearly and evade behaviors that may lead to the reduction of marital intimacy and satisfaction such as contempt, criticism, blame, and sarcasm (8).…”
Section: Discussionmentioning
confidence: 99%
“…Intimacy is defined as the closeness, similarity and romantic or emotional personal relationship, which requires a deep understanding and perception of the other person for expressing thoughts and feelings (4). Marital intimacy in the couple's relationship leads to the enhancement of marital compatibility (5), marital satisfaction (6,7), increase of the quality of marital life (8), feeling of welfare (9), and a decrease of daily stress (10). On the other hand, the lack of intimacy in young couples is one of the predictors of divorce in old age (11).…”
Section: Introductionmentioning
confidence: 99%
“…Therapists have described on various aspects that may negatively influence marital stability such as communication difficulty, unrealistic expectations from marriage and the spouse, lack of intimacy, and lack of expressing affection ( Motavali, Ozgoli, Bakhtiari, & Alavimajd, 2010 ; Shahrestany, Doustkam, Rahbarda, & Mashhadi, 2013 ). Taking the fact for the granted that in many societies today family is the prominent source of comfort for people and taking the fact that in the modern society the family is faced with the challenges, the most important of which is the loss of marital intimacy, into account, an interventional program is helpful to prevent these problems and heighten intimacy ( Farbod, Ghamari, & Majd, 2014 ). To enhance () intimacy in couples, educational approaches may support () ( Oulia, Fatehizadeh, & Bahrami, 2006 ).…”
Section: Introductionmentioning
confidence: 99%
“…Studies on quality of life have shown that quality of life is related to marital intimacy (15,16). Barzegar and Samani (17) and the training of the communication skills program (18,19,20,21,22,23); and training on the program for the enrichment of relations (24,25,26) on quality of life which has had an effect on the quality of life of individuals and has led to an improvement in the quality of life of individuals.…”
Section: Introductionmentioning
confidence: 99%